REFLECTION ON ISLAMIC AGRICULTURAL POLICIES DURING THE UMAYYAD DYNASTY AND CONTEMPORARY INDONESIA - Putri Vella Meliyanti; Sarirotul 'Alim; Mohammad Aswad; Muhammad Aqim Adlan (Nurul Jadid University, 2025)
This study examines Islamic agricultural policies during the Umayyad Dynasty and compares them with contemporary agricultural policies in Indonesia. Agriculture has historically played a strategic role not only as an economic sector but also as an instrument for social justice and public welfare. During the Umayyad period (661–750 CE), agricultural policy was based on Islamic principles emphasizing distributive justice, land productivity, and sustainable resource management through instruments such as kharaj, ushr, land reform, and irrigation development. In contrast, modern Indonesia faces structural challenges in agriculture, including unequal land ownership, low farmer welfare, climate change, and food security issues, which are addressed through agrarian reform, subsidies, infrastructure development, and technological innovation. This research employs a qualitative descriptive method with a comparative-historical approach, using literature studies from classical Islamic sources, academic journals, and contemporary policy documents. The analysis focuses on institutional structures, land ownership systems, fiscal instruments, infrastructure, and socio-economic impacts. The findings indicate that despite differing socio-political contexts, both systems share similar objectives in promoting public welfare and agricultural sustainability. The values of justice (‘adl), equitable distribution, and moral responsibility embedded in Umayyad agricultural policies remain relevant and can provide normative insights for strengthening contemporary Indonesian agricultural policy. Integrating these Islamic ethical principles may contribute to more inclusive, sustainable, and socially oriented agricultural development in Indonesia.